2020
DOI: 10.3389/fnmol.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Event-Related Transients: Confidence Intervals, Permutation Tests, and Consecutive Thresholds

Abstract: Fiber photometry has enabled neuroscientists to easily measure targeted brain activity patterns in awake, freely behaving animal. A focus of this technique is to identify functionally-relevant changes in activity around particular environmental and/or behavioral events, i.e., event-related activity transients (ERT). A simple and popular approach to identifying ERT is to summarize peri-event signal [e.g., area under the curve (AUC), peak activity, etc.,] and perform standard analyses on this summary statistic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 15 publications
0
73
0
Order By: Relevance
“…During Pre-Training, when there were high numbers of both correct and incorrect nose pokes, there was a large increase in ACh release following correct nose pokes, which were followed by reward delivery and receptacle light, but not incorrect nose pokes ( Figure 2C + Figure 2—figure supplement 1B–C ). We used bootstrapped confidence intervals (bCIs) to determine when transients were statistically significant (bCI did not contain the null of 0 [ Jean-Richard-Dit-Bressel et al, 2020 ]). Correct, but not incorrect, nose poke trials consistently showed a sustained, significant increase in fluorescence close to the time of nose poke onset ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During Pre-Training, when there were high numbers of both correct and incorrect nose pokes, there was a large increase in ACh release following correct nose pokes, which were followed by reward delivery and receptacle light, but not incorrect nose pokes ( Figure 2C + Figure 2—figure supplement 1B–C ). We used bootstrapped confidence intervals (bCIs) to determine when transients were statistically significant (bCI did not contain the null of 0 [ Jean-Richard-Dit-Bressel et al, 2020 ]). Correct, but not incorrect, nose poke trials consistently showed a sustained, significant increase in fluorescence close to the time of nose poke onset ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Bootstrapped confidence intervals (bCIs) of the Z-scored % ΔF/F0 fiber photometry data within and across mice were generated using the methods described in Jean-Richard-Dit-Bressel et al, 2020 for the following events: tone onset, correct nose poke, receptacle entry, and incorrect nose poke. For the within-mouse analysis by day, trials were aligned to event onset, and bCIs were generated for events that had at least 3 trials from 5 s before to 10 s after each event.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, bootstrapped means were obtained by randomly resampling from subject mean waveforms with replacement (1000 iterations). CI limits were derived from 2.5 and 97.5 percentiles of bootstrap distribution, expanded by a factor of (Jean-Richard-dit-Bressel et al, 2020). A significant transient was identified as a period that CI limits did not contain 0 (moving average baseline) for at least 1/3secs (low-pass filter window; Jean-Richard-dit-Bressel et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…First, DF/F within a time window around events was compiled. To determine significant event-related transients within this window, a bootstrapping CI procedure (95% CI, 1000 bootstraps) was used (Jean-Richard-dit-Bressel et al, 2020). A distribution of bootstrapped DF/F means was generated by randomly resampling from trial DF/F waveforms, with replacement, for the same number of trials.…”
Section: Experimental Design and Statistical Analysesmentioning
confidence: 99%
“…A distribution of bootstrapped DF/F means was generated by randomly resampling from trial DF/F waveforms, with replacement, for the same number of trials. A CI was obtained per time point using the 2.5 and 97.5 percentiles of the bootstrap distribution, which was then expanded by a factor of sqrt (n/(n -1)) to adjust for narrowness bias (Jean-Richard-dit-Bressel et al, 2020). Significant transients were defined as periods whose 95% CI did not contain 0 (baseline) for at least 0.5 s (low-pass filter threshold).…”
Section: Experimental Design and Statistical Analysesmentioning
confidence: 99%